High-capacity adenovector delivery of forced CRISPR-Cas9 heterodimers fosters precise chromosomal deletions in human cells - Francesca Tasca; Marcella Brescia; Jin Liu; Josephine M. Janssen; Kamel Mamchaoui; Manuel A.F.V. Gonçalves (Elsevier, 2023)
Genome editing based on dual CRISPR-Cas9 complexes (multiplexes) permits removing specific genomic sequences in living cells leveraging research on functional genomics and genetic therapies. Delivering the required large and multicomponent reagents in a synchronous and stoichiometric manner remains, however, challenging. Moreover, uncoordinated activity of independently acting CRISPR-Cas9 multiplexes increases the complexity of genome editing outcomes. Here, we investigate the potential of fostering precise multiplexing genome editing using high-capacity adenovector particles (AdVPs) for the delivery of Cas9 ortholog fusion constructs alone (forced Cas9 heterodimers) or together with their cognate guide RNAs (forced CRISPR-Cas9 heterodimers). We demonstrate that the efficiency and accuracy of targeted chromosomal DNA deletions achieved by single AdVPs encoding forced CRISPR-Cas9 heterodimers is superior to that obtained when the various components are delivered separately. Finally, all-in-one AdVP delivery of forced CRISPR-Cas9 heterodimers triggers robust DMD exon 51 splice site excision resulting in reading frame restoration and selection-free detection of dystrophin in muscle cells derived from Duchenne muscular dystrophy patients. In conclusion, AdVPs promote precise multiplexing genome editing through the integrated delivery of forced CRISPR-Cas9 heterodimer components, which, in comparison with split conventional CRISPR-Cas9 multiplexes, engage target sequences in a more coordinated fashion.